Unusual associations of bilateral Morgagni hernia in a child with Down’s syndrome: a case report - Shayba, Nabil Ahmed; Malkani, Izzat; Shaikh, Mishraz; Alshamiri, Kamal Mostafa (International Surgery Journal, 2024)
Morgagni hernia is a rare form of congenital diaphragmatic hernia. It is associated with Down’s syndrome as well as other congenital anomalies. Pediatric patients usually present with respiratory manifestations, the clinical presentation of Morgagni hernia is non-specific. Therefore, Morgagni hernia is mainly diagnosed by radiological imaging. The rarity of this type of hernia along with the vague clinical presentation can lead to missed diagnosis.